Effects of Sensory Integration with Neuro developmental Technique (NDT) on Gross Motor Function in Cerebral Palsy Children: A Pilot Study - Malawade, Mandar; G. Varadharajulu, G. Varadharajulu (Journal of Neonatal Surgery, 2025)
Background: Cerebral palsy (CP) often results in motor and sensory impairments that limit functional independence. Sensory Integration Therapy (SIT) and Neurodevelopmental Treatment (NDT) are commonly used in pediatric rehabilitation. While both approaches individually show promise in enhancing gross motor function, limited evidence exists on their combined effect. This pilot study evaluates the efficacy of integrating SIT with NDT on gross motor performance in children with CP. Aim and Objectives: To assess the impact of combined Sensory Integration and Neurodevelopmental Therapy on gross motor function in children with cerebral palsy using the BOT-2 Short Form as an outcome measure. Methodology: Twelve children with cerebral palsy (aged 4–10 years; including spastic diplegic, ataxic, and hypotonic subtypes) were selected based on predefined inclusion and exclusion criteria. Each child underwent a combined SIT and NDT intervention for 6 weeks, 3 days per week. Pre- and post-treatment scores were measured using the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2), Short Form. Data were analyzed using a paired t-test. Results: All participants showed improvement in gross motor scores. The mean difference in BOT-2 scores was 6.17 ± 0.84. Statistical analysis using a paired t-test revealed significant improvement post-intervention (t = 25.6, p < 0.05), indicating consistent functional gains across the group. Conclusion: The combination of Sensory Integration and Neurodevelopmental Therapy resulted in significant improvements in gross motor function in children with cerebral palsy. These findings support the potential of integrated sensory-motor approaches in early pediatric rehabilitation and suggest the need for further large-scale studies.